You've written "then" before 3, so i assume the real question is:
(40 * 40 * 40 + 26 - 98 + 45 * 78 * 78 * 78) / 3
Use "PEMDAS" first solve under the parenthesis, then after it.
= (64000 + 26 - 98 + 21354840) / 3
= 21418768 / 3
= 7139589.33
In short, Your Answer would be: 7139589.33
Hope this helps!
Answer:
The sum is equal to 5
Step-by-step explanation:
we know that
The algebraic expression of the phrase " the sum of negative two squared plus one" is equal to
![(-2)^{2}+1\\=4+1\\=5](https://tex.z-dn.net/?f=%28-2%29%5E%7B2%7D%2B1%5C%5C%3D4%2B1%5C%5C%3D5)
Answer:
![-6x+15](https://tex.z-dn.net/?f=-6x%2B15%3C10-5x)
Step-by-step explanation:
![-3(2x-5)](https://tex.z-dn.net/?f=-3%282x-5%29%3C5%282-x%29)
Distribute.
![-6x+15](https://tex.z-dn.net/?f=-6x%2B15%3C10-5x)
Add 5x and subtract 15 on both sides.
![-6x-5x](https://tex.z-dn.net/?f=-6x-5x%3C10-15)
![-1x](https://tex.z-dn.net/?f=-1x%3C-5)
Multiply -1 on both sides.
![x>5](https://tex.z-dn.net/?f=x%3E5)
Answer:
-9
Step-by-step explanation:
Four consecutive odd integers be (2x - 3),(2x -1),(2x + 1),(2x + 3)
2x-3 + 2x - 1 +2x+1 + 2x+3 = -48
2x + 2x + 2x +2x - 3 - 1 + 3 + 1 = -48
8x = -48
x = -48/8
x = -6
Least of these integer = 2x + 3 = 2*(-6) + 3 = -12 + 3 = -9